Use and Outcomes of Minimally Invasive Hysterectomy for Women with Non-Endometrioid Endometrial Cancers - NIETO, Vanessa L. (Am J Obstet Gynecol, 2018)
BACKGROUND: Minimally invasive hysterectomy is now routinely used for women with uterine cancer. Most studies of minimally invasive surgery (MIS) for endometrial cancer have focused on low-risk, endometrioid tumors with few reports of the safety of the procedure for women with higher risk histologic subtypes. OBJECTIVE: To examine the utilization and survival associated with minimally invasive hysterectomy for women with uterine cancer and high-risk histologic subtypes. STUDY DESIGN: We used the National Cancer Database was used to identify women with stages I-III uterine cancer who underwent hysterectomy from 2010-2014. Women with serous, clear cell carcinomas and sarcomas were examined. Women who had laparoscopic or robotic-assisted hysterectomy were compared to those who underwent open abdominal hysterectomy. After a propensity score inverse probability of treatment weighted analysis, the effect of MIS hysterectomy on overall, 30-day, and 90-day mortality was examined for each histologic subtype of uterine cancer. RESULTS: Of 94,507 patients identified, 64,417 (68.2%) underwent minimally invasive hysterectomy. Among women with endometrioid tumors (n=81,115), 70.8% underwent MIS hysterectomy. The rates of MIS in those with non-endometrioid tumors (n=13,392) was 57.6% for serous carcinomas, 57.0% for clear cell tumors, 47.3% for sarcomas, 32.2% for leiomyosarcomas, 47.9% for stromal sarcomas and 48.5% for carcinosarcomas. Performance of MIS increased across all histologic subtypes between 2010 and 2014. For non-endometrioid subtypes, robotic-assisted procedures accounted for 47.9%-75.7% of MIS hysterectomies by 2014. In a multivariable model, women with non-endometrioid tumors were less likely to undergo MIS than those with endometrioid tumors (P<0.05). There was no association between route of surgery and 30-day, 90-day, or overall mortality for any of the non-endometrioid histologic subtypes. CONCLUSIONS: The use of minimally invasive surgery is increasing rapidly for women with stage I-III non-endometrioid uterine tumors. Performance of minimally invasive surgery does not appear to adversely impact survival. CONDENSATION: The use of minimally invasive surgery for women with stage I-III non-endometrioid uterine tumors does not appear to adversely impact survival.